Improved rehabilitation and training techniques through the use of motion simulation - Core strength conditioning for elite rowers - Sawade, C.; Turnock, S.; Forrester, A.; Toward, M. (Procedia Engineering, 2012)
The most common injuries experienced by sweep rowers relate to the lower back; rowers with greater core strength have been shown to be less prone to these injuries. Stationary rowing trainers (Ergometers) currently used for training and rehabilitation generally have a fixed support base, contrary to a real boat. It is hypothesized that training with an unstable base may help develop core strength in athletes. This paper describes early development of a rowing simulator with a realistic unstable platform. Using SolidWorks, a conceptual motion simulator was designed, which was then linked to MATLAB/Simulink to produce a controllable simulation of rowing. A control algorithm was developed to compute the forces and virtual rowing parameters required. The algorithm uses a PID controller to maintain a coordinate position of the virtual boat's centre of gravity. In particular, the issue of creating an "unstable" feeling about the roll axis was developed. Comparison between the simulated output and real rowing data is required for verification of effective control. The resultant control system could be linked to a real-time motion platform, whereby EMG and or other biometric measurements could be used to determine the effectiveness of core muscle activation between the simulator, Ergometer and on water rowing.